Marketing Mix Kepusan Konsumen Modern Retail Stores - Taufan Eka Putralasabuda; Muhammad junaid kamaruddin (Economy Deposit Journal (E-DJ), 2022)
The research aims to determine the determinants of the success of modern retail or minimarket groups and their attractiveness to consumers. This research is a literature review research from scientific studies. The research subjects are consumers from modern retail/minimarkets with the objects of this research being all modern retail/minimarkets. A systematic, explicit and reproducible method for identifying, evaluating and synthesizing research results and ideas with a literature search was carried out in the ScienceDirect, Emerald Insight, Proquest, Sage, Google Scholar databases using the keywords Marketing Mix, modern retail, traditional retail and modern retail consumers. The results of this research show that consumers feel that modern retail has relatively low prices and a variety of products but with consistent quality. Shopping becomes more comfortable because the environment provided by supermarkets is a comfortable place and a conducive shopping environment and finds that attractive interior displays influence consumer satisfaction. Promotion is also an important part of the main factors that will determine customer loyalty. Modern retail promotion techniques can also help maintain customer loyalty and attract new customers to switch from traditional retail